Influence of rumen fluid inoculation on incidence of sickness in newly arrived feeder calves - Bolsen, K.K.; Armbruster, S.; Caley, Homer K., 1922-; Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Inoculating newly arrived feeder calves with 250 ml. rumen fluid did not stimulate weight gain or decrease sickness. One hundred seventy steer calves were used in the 31 day study.
Keywords: Beef; Rumen; Calves; Sickness; Weight gain